Fabricação de estruturas de pasta de cimento Portland com porosidade orientada por freezing-casting - Leandro Henrique Moura Silva (2018)
Portland cement has been a material used in civil construction since its discovery until today. Its characteristics and properties are already well known, widespread and used all over the planet. Every day new uses and applicability of the cement are discovered. An example of this is that the presence of porosity in the cement can enable the emergence of new applications, such as thermal insulation, acoustic, some specific types of filters to separate phases and perform water desalination, fabrication of permeable pavements, as well as in some segments of researches that need materials with controlled and dimensioned pores. The process to produce the porous material is principally responsible to its unique structures and properties. Among others, there is a process to structure oriented porosity that has been very widespread nowadays and that has presented good results with its use: the freeze-casting. This process enables the porosity orientation, following the temperature gradient, by freezing a fluid suspension with a certain concentration of solid particles. In this context, several proportions of water, cement and dispersant, were studied to find the proportions that made the solution as fluid as possible, to facilitate and allow the orientation of the porosity through solidification in freezer or using liquid nitrogen. The specimens were tested to characterize their density, total porosity (number of voids), compression strength test and 3D structures by x-ray microtomography. The results were promising, the orientation process applied to the cement was a success and demonstrated an increase of the compressive strength of the freeze-casting oriented samples with liquid nitrogen, when compared to the conventional process, as well as an increase in the open porosity of the structure.